Fusions involving protein kinase C and membrane-associated proteinsin benign fibrous histiocytoma - Płaszczyca, Anna; Nilsson, Jenny; Magnusson, Linda; Brosjö, Otte; Larsson, Olle; Vult von Steyernd, Fredrik; Domanski, Henryk A.; Lilljebjörn, Henrik; Fioretos, Thoas; Tayebwa, Johnbosco; Mandahl, Nils; Nord, Karolin H.; et al. (he International Journal of Biochemistry & Cell Biology, 2014)
Benign fibrous histiocytoma (BFH) is a mesenchymal tumor that most often occurs in the skin (so-called dermatofibroma), but may also appear in soft tissues (so-called deep BFH) and in the skeleton(so-called non-ossifying fibroma). The origin of BFH is unknown, and it has been questioned whether itis a true neoplasm. Chromosome banding, fluorescence in situ hybridization, single nucleotide polymor-phism arrays, RNA sequencing, RT-PCR and quantitative real-time PCR were used to search for re current somatic mutations in a series of BFH. BFHs were found to harbor recurrent fusions of genes encoding membrane-associated proteins (podoplanin, CD63 and LAMTOR1) with genes encoding protein kinaseC (PKC) isoforms PRKCB and PRKCD. PKCs are serine–threonine kinases that through their many phos-phorylation targets are implicated in a variety of cellular processes, as well as tumor development. When inactive, the amino-terminal, regulatory domain of PKCs suppresses the activity of their catalytic domain. Upon activation, which requires several steps, they typically translocate to cell membranes, where they interact with different signaling pathways. The detected PDPN-PRKCB, CD63-PRKCD and LAMTOR1-PRKCDgene fusions are all predicted to result in chimeric proteins consisting of the membrane-binding part of PDPN, CD63 or LAMTOR1 and the entire catalytic domain of the PKC. This novel pathogenetic mechanism should result in constitutive kinase activity at an ectopic location. The results show that BFH indeed is atrue neoplasm, and that distorted PKC activity is essential for tumorigenesis. The findings also provide means to differentiate BFH from other skin and soft tissue tumors.
Keywords: Cell membrane; Endosomes; Gene fusion; Podoplanin; CD63; LAMTOR1